Rod electrical coupling is controlled by a circadian clock and dopamine in mouse retina - Jin, Nan Ge; Chuang, Alice Z.; Masson, Philippe J.; Ribelayga, Christophe P. (The Journal of physiology, 2015)
Key points Rod photoreceptors play a key role in vision in dim light; in the mammalian retina, although rods are anatomically connected or coupled by gap junctions, a type of electrical synapse, the functional importance and regulation of rod coupling has remained elusive. We have developed a new technique in the mouse: perforated patch‐clamp recording of rod inner segments in isolated intact retinae maintained by superfusion. We find that rod electrical coupling is controlled by a circadian clock and dopamine, and is weak during the day and stronger at night. The results also indicate that the signal‐to‐noise ratio for a dim light response is increased at night because of coupling. Our observations will provide a framework for understanding the daily variations in human vision as well as the basis of specific retinal malfunctions. Rod single‐photon responses are critical for vision in dim light. Electrical coupling via gap junction channels shapes the light response properties of vertebrate photoreceptors, but the regulation of rod coupling and its impact on the single‐photon response have remained unclear. To directly address these questions, we developed a perforated patch‐clamp recording technique and recorded from single rod inner segments in isolated intact neural mouse retinae, maintained by superfusion. Experiments were conducted at different times of the day or under constant environmental conditions, at different times across the circadian cycle. We show that rod electrical coupling is regulated by a circadian clock and dopamine, so that coupling is weak during the day and strong at night. Altogether, patch‐clamp recordings of single‐photon responses in mouse rods, tracer coupling, receptive field measurements and pharmacological manipulations of gap junction and dopamine receptor activity provide compelling evidence that rod coupling is modulated in a circadian manner. These data are consistent with computer modelling. At night, single‐photon responses are smaller due to coupling, but the signal‐to‐noise ratio for a dim (multiphoton) light response is increased at night because of signal averaging between coupled rods.